Microstructures, mechanical properties and oxidation behaviour of single-phase Fe3Al (D03) and two-phase α-Fe, Al (A2) + Fe3Al (D03) FeAlV alloys. (June 2016) - Senčekova, L.; Palm, M.; Pešička, J.; Veselý, J.
Abstract: Microstructures, mechanical properties and oxidation behaviour of single-phase Fe3 Al (D03 ) and two-phase α-Fe, Al (A2) + Fe3 Al (D03 ) FeAlV alloys have been studied. Alloying with vanadium substantially increases the strength of the single-phase alloys through solid solution hardening. In addition, vanadium markedly increases the D03 /B2 transition temperature. The change from B2 to D03 at a given temperature yields an additional increase in strength. The two-phase alloys have a fine-scaled coherent microstructure with D03 precipitates ranging between 10 and 30 nm in the as-cast state. However, marked coarsening of D03 is observed after annealing at 700 °C for 1000 h. Up to this temperature the alloys show an appreciable flow stress and creep strength, comparable to those of other iron aluminide based alloys with coherent microstructures. Oxidation tests at 700–900 °C revealed formation of thick and porous Fe2 O3 + Al2 O3 scales above 700 °C. Therefore, above 700 °C the oxidation behaviour of these alloys is inferior compared to that of other iron aluminide alloys with about the same Al content. This poor oxidation behaviour does not improve when 4–8 at.% Cr are added. Highlights: First detailed investigation of mechanical properties and oxidation of FeAlV alloys. Single-phase D03 FeAlV show marked solid solution hardening. Coherent A2 + D03 FeAlV alloys show high strength up to 700 °C. Oxidation resistance limited up to 700 °C.